Old vs recent cross-border cooperation: Portugal-Spain and Norway-Sweden - Medeiros, Eduardo José Rocha (2019)
The two largest European Peninsulas (Iberian and Scandinavian) are both divided by a long and ancient frontier, which separates four old European nations: Portugal, Spain, Sweden and Norway. In the first case, the unusual stability of the border, which remains almost unchanged for more than 800 years, has contributed to strengthen a long ‘back-to-back’ existence, during most of this time. In the latter, however, successive changes in the border location, and historical alliances between the Nordic countries, created a more ‘face-to-face’ type of border and a more solid background for the cross-border cooperation (CBC). Therefore, while the INTERREG-A Community Initiative represented an important starting point for the CBC process in most parts of the Portuguese–Spanish border region (PSBR), it was just another important added value for the CBC in the Swedish–Norwegian border region (SNBR), since this process had already started in 1948, when Sweden, Norway, Iceland and Denmark established the joint Nordic Committee for Economic Cooperation, followed by the formation of the Nordic Council in 1951. With this in mind, this article analyses how such distinct CBC backgrounds contributed to the two different approaches and results obtained from the implementation of the INTERREG-A in both studied border regions.